2018
DOI: 10.3390/nu10101548
|View full text |Cite
|
Sign up to set email alerts
|

Low-Salt Intake Suggestions in Hypertensive Patients Do not Jeopardize Urinary Iodine Excretion

Abstract: A low-sodium diet is an essential part of the treatment of hypertension. However, some concerns have been raised with regard to the possible reduction of iodine intake during salt restriction. We obtained 24-h urine collections for the evaluation of iodine (UIE) and sodium excretion (UNaV) from 136 hypertensive patients, before and after 9 ± 1 weeks of a simple low-sodium diet. Body mass index (BMI), blood pressure (BP), and drug consumption (DDD) were recorded. Data are average ± SEM. Age was 63.6 ± 1.09 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Results from a salt intervention study in children and their families in northern China demonstrated that ≈25% reduction in salt intake does not compromise iodine status [17]. Reduction of ≈18% in patients on antihypertensive treatment in Italy did not significantly reduce iodine excretion [19]. These data confirm the lack of conflict between population-wide strategies of decreasing salt intake and adequate iodized salt consumption and are in line with our data, where subjects reduced salt intake with approximately 30%.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results from a salt intervention study in children and their families in northern China demonstrated that ≈25% reduction in salt intake does not compromise iodine status [17]. Reduction of ≈18% in patients on antihypertensive treatment in Italy did not significantly reduce iodine excretion [19]. These data confirm the lack of conflict between population-wide strategies of decreasing salt intake and adequate iodized salt consumption and are in line with our data, where subjects reduced salt intake with approximately 30%.…”
Section: Discussionsupporting
confidence: 86%
“…Literature that links habitual salt intake to urinary iodine excretion is scarce [12,13,14,15,16,17,18,19] and generalization of results is difficult because of differences in dietary sources of iodine. In a survey in Samoa, no detectable difference in iodine intake in population subgroups defined by salt intake above or below 5 g/d was found [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in recent surveys in northeastern Italy, 70-80% of families declared that they used iodized salt daily [9,11], while in a study conducted in Calabria the percentage of families using iodized salt was 64-82% in rural-urban areas [23]. Of the 136 subjects attending our Center for Secondary Hypertension, 62% declared using iodized salt, since, at the beginning of the study, all these patients had had a consultation with a dietitian and had received written nutritional advice [16].…”
Section: Discussionmentioning
confidence: 96%
“…However, we have very little direct information on the iodine intake of the adult population of Liguria. In 2018, in a cohort of 136 adults referred to our Center for Secondary Hypertension, we observed that, after salt restriction (by avoiding preserved foods), 24-h iodine excretion showed a non-significant decrease [16]. Indeed, 24-h iodine excretion lower than 100 µg was recorded in only 28 subjects (21%), suggesting an average iodine sufficiency in this cohort [16].…”
Section: Introductionmentioning
confidence: 83%